Implementation of agile approach in developing drug education application in pharmacy environment: a case study on improving user knowledge - Sihombing, Denny Jean Cross (Jurnal Info Sains : Informatika dan Sains, 2024)
The development of drug counseling and education system applications in pharmacies is an important initiative, given the challenges in providing effective drug education to users. This research addresses these issues using an Agile approach in application development. The research methods include user requirements analysis, iterative development of the application using Agile methodology, and evaluation of functionality and user acceptance. The results showed that the application of the Agile approach in developing this application successfully increased user engagement and positively contributed to improving health services in pharmacies. The contribution of this research lies in developing adaptive, responsive, and effective health applications that meet user needs and improve the quality of health services in pharmacies. Thus, this research provides a better understanding of innovative approaches in health app development and highlights the importance of implementing best practices in improving public health services.